JURIDICAL ANALYSIS OF APPLICATION OF NARCOTIC REHABILITATION THROUGH INTEGRATED ASSESSMENT OF NARCOTICS ABUSERS IN THE RIAU ISLANDS (Research Study at the National Narcotics Agency of the Riau Islands Province) - Indriyani, Ika; Respationo, Soerya; Fadlan, Fadlan (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
The aspect of punishment given to Narcotics Addicts is intended to provide treatment (treatment) and improvement (rehabilitation) not just punishment. Because basically narcotics abusers or addicts are perpetrators of narcotics abuse crimes as well as victims of their own actions. the legal arrangement for the application of narcotics rehabilitation through an integrated assessment of narcotics abusers in the Riau Islands (Research Study at the National Narcotics Agency of the Riau Islands Province) has been running as expected, but the facts on the ground still encounter obstacles. , especially in law enforcement. Therefore, it is hoped that law enforcers can carry out their duties optimally so that the obstacles they face can be minimized.